Chronic Myelogenous Leukemia Diagnosed in the Setting of Untreated Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma. (April 2020) - Viswanathan, Kartik; Roboz, Gail; Chadburn, Amy; Mathew, Susan
Chronic myeloid leukemia (CML) is rarely reported to occur in treated chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL). In this article, we report a woman in her 70s, diagnosed with CLL/SLL in 2000, untreated, who subsequently presented 12 years later with de novo CML, BCR-ABL1+ . Her IGHV mutated CLL/SLL based on the initial sample in our laboratory showed homozygous and heterozygous 13q14.3 deletions, whereas her CML, at presentation, showed a 46, XX, t(9;22)(q34;q11.2)[7]/46, XX[18] karyotype with a p190 BCR-ABL1 transcript. The tumor burden of each clone varied with treatment, including when treated with dasatinib, used to target both clones. In addition, the cytogenetic abnormalities evolved over time and treatments and included acquisition of an extra chromosome 8 in the CML clone and a novel K1992T ATM missense mutation (47% allele frequency) in the CLL/SLL clone. The patient's last bone marrow biopsy, 5 years after her CML diagnosis and 17 years after the CLL/SLL diagnosis, showed residual CML with extensive involvement by CLL/SLL (80%). Cytogenetic studies showed a 46, XX karyotype, while FISH identified 13q14.3 deletion and the BCR-ABL1 translocation in the CLL/SLL and CML clones, respectively. To date, this is the fourth case of concurrent CML, BCR-ABL1+ arising in untreated CLL/SLL. Here we show dynamic variation in the size of the 2 clonal processes reflecting the variable responsiveness to specific therapies. In addition to the unusual BCR-ABL1 + p190 transcript in the patient's CML, a novel ATM K1992T mutation was identified in the CLL/SLL population.